2017
DOI: 10.3390/ijerph14030226
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Ambient Air Pollution and Allergic Rhinitis: Further Epidemiological Evidence from Changchun, Northeastern China

Abstract: With the continuous rapid urbanization process over the last three decades, outdoors air pollution has become a progressively more serious public health hazard in China. To investigate the possible associations, lag effects and seasonal differences of urban air quality on respiratory health (allergic rhinitis) in Changchun, a city in Northeastern China, we carried out a time-series analysis of the incidents of allergic rhinitis (AR) from 2013 to 2015. Environmental monitoring showed that PM2.5 and PM10 were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 49 publications
1
38
0
1
Order By: Relevance
“…40 Moreover, we found that PM 10 outside the schools (mean 168 µg/m 3 ) was associated with onset of rhinitis. This is in agreement with previous prevalence studies reporting associations between childhood rhinitis and outdoor PM 10 in Changchun, China, 18 in Shanghai, 19 and in a six cities study among school children in France. 41 The proposed mechanism could be neutrophilic inflammation in the nasal mucosa.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…40 Moreover, we found that PM 10 outside the schools (mean 168 µg/m 3 ) was associated with onset of rhinitis. This is in agreement with previous prevalence studies reporting associations between childhood rhinitis and outdoor PM 10 in Changchun, China, 18 in Shanghai, 19 and in a six cities study among school children in France. 41 The proposed mechanism could be neutrophilic inflammation in the nasal mucosa.…”
Section: Discussionsupporting
confidence: 93%
“…In China, outdoor air pollution is an important issue and has been demonstrated to be associated with rhinitis. A time series analysis from Changchun (northeastern China) found an increase in allergic rhinitis outpatient visits during days with higher outdoor concentrations of PM 2.5 , PM 10 , SO 2 , and NO 2 . A nationwide cross‐sectional study from Taiwan found associations between outdoor NOx, CO, and SO 2 and allergic rhinitis among school children .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another meta-analysis that used largely the same cohort data also found no evidence that PM2.5 and NO2 exposure increases the risk for allergic rhinitis [51]. A number of recently published results from Chinese cross-sectional studies report positive links between PM2.5 and NO2 and allergic rhinitis in children [52][53][54]. It is not possible to conclusively assess to what extent the methodological weaknesses of a cross-sectional study, regional and cultural lifestyle factors, or, lastly, the significantly higher exposure levels in China are decisive for the differing results compared with the European and North American studies.…”
Section: Allergic Rhinitismentioning
confidence: 98%
“…Recent studies have shown an association between high levels of air pollution and an increased risk of allergic sensitization, as well as between high levels of air pollution and prevalence of AR . Teng et al . revealed that the prevalence of AR was significantly associated with levels of PM2.5, PM 10 µm in diameter (PM10), SO 2 , and NO 2 in a large population‐based sample.…”
Section: Discussionmentioning
confidence: 99%